Implementation of lesson study based on transcript-based lesson analysis on student learning activity - Riana, Puspa Cantika; Syamsurizal, Syamsurizal; Haryanto, Haryanto (IAIN Palangka Raya, 2024)
The research was conducted to determine the effect of implementing a lesson study based on transcript-based lesson analysis on students' active learning, which was carried out using mixed methods. The population in this study were class VIII students at Al-Falah Islamic Middle School, Jambi City, with a sample of 25 students, namely 12 female students and 13 male students, selected using a non-probability sampling technique. The efforts made in this research were to apply lesson study in three stages, namely, planning, implementation, and reflection. Data collection in this study used observation, video/audio documentation, and observation sheets on student learning activities carried out in 2 lesson study cycles. The results obtained in cycle 1 showed that the teacher dominated the overall learning, but the students were also quite active. Meanwhile, in cycle 2, students dominate more in the learning process, which can be seen from the four indicators of student learning activity, whose activity category is better than in cycle 1. Implementing lesson study based on transcript-based lesson analysis can increase student learning activity.